Simple non-invasive fibrosis scoring systems can reliably exclude advanced fibrosis in patients with non-alcoholic fatty liver disease. Issue 9 (26th August 2010) - McPherson, Stuart; Stewart, Stephen F; Henderson, Elsbeth; Burt, Alastair D; Day, Christopher P
Abstract : Background: Accurate evaluation of liver fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) is important to identify patients who may develop complications. The aim of this study was to compare the diagnostic performance of simple non-invasive tests in identifying advanced fibrosis among patients with biopsy-proven NAFLD. Methods: Consecutive patients with biopsy proven NAFLD were recruited from the Newcastle Hospitals Fatty Liver Clinic from 2003 to 2009. The AST/ALT ratio, AST to platelet ratio index, BARD (weighted sum of BMI>28=1 point, AST/ALT ratio>0.8=2 points, diabetes=1 point), FIB-4 (age×AST (IU/l)/platelet count (×10 9 /litre)×√ALT (IU/l)) and NAFLD fibrosis scores were calculated from blood tests taken at time of biopsy. Results: 145 patients (82 male (61%), mean age 51±12 years) were included. The mean body mass index was 35±5 kg/m 2 . 73 subjects (50%) had diabetes. 93 patients (64%) had non-alcoholic steatohepatitis. 27 (19%) had advanced fibrosis (Kleiner stage 3–4). The FIB-4 score had the best diagnostic accuracy for advanced fibrosis (area under receiver operator characteristic curve (AUROC) 0.86), followed by AST/ALT ratio (AUROC 0.83), NAFLD fibrosis score (AUROC 0.81), BARD (AUROC 0.77) and AST to platelet ratio index (AUROC 0.67). The AST/ALT ratio, BARD score, FIB-4 and NAFLD fibrosis scores had negative predictive values greater than 90% (93%, 95%, 95% and 92% respectively). Positive predictive values were modest. In order to exclude advanced fibrosis liver biopsy could potentially be avoided in 69% with AST/ALT ratio, 62% with FIB-4, 52% with NAFLD fibrosis score and 38% with BARD. Conclusions: The ALT/AST ratio, FIB-4 and NAFLD fibrosis scores can reliably exclude advanced fibrosis in a high proportion of patients with NAFLD, allowing liver biopsy to be used in a more directed manner.